2021
DOI: 10.3892/ol.2021.12470
|View full text |Cite
|
Sign up to set email alerts
|

Identification of AKT1/β-catenin mutations conferring cetuximab and chemotherapeutic drug resistance in colorectal cancer treatment

Abstract: In anticancer therapy, the effectiveness of therapeutics is limited by mutations causing drug resistance. KRAS mutations are the only determinant for cetuximab resistance in patients with colorectal cancer (CRC). However, cetuximab treatment has not been fully successful in the majority of patients with wild-type (WT) KRAS. Therefore, it is important to determine new predictive mutations in CRC treatment. In the present study, the association between AKT1/β-catenin (CTNNB1) mutations with the drug resistance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…The top 20 genes with the highest mutation rates in both scoring subgroups were identified, and all of these genes had mutation rates above 10%. Previous studies have shown that KRAS mutation can act as a biomarker of EGFR-targeted monoclonal antibody resistance in colon cancer patients and is associated with metastasis and poor prognosis ( 36 , 37 ). In our study, KRAS mutation frequency ranked fourth in both high and low NRS-score groups.…”
Section: Resultsmentioning
confidence: 99%
“…The top 20 genes with the highest mutation rates in both scoring subgroups were identified, and all of these genes had mutation rates above 10%. Previous studies have shown that KRAS mutation can act as a biomarker of EGFR-targeted monoclonal antibody resistance in colon cancer patients and is associated with metastasis and poor prognosis ( 36 , 37 ). In our study, KRAS mutation frequency ranked fourth in both high and low NRS-score groups.…”
Section: Resultsmentioning
confidence: 99%
“…As the second hypothesis, SW480 cells have several mutations in the TP53 gene while HCT116 harbored WT TP53. 38 , 41 Moreover, HCT116 showed lower BCL-2 family activity compared with SW480 cells. 42 Furthermore, previous research has reported the M-protein effects on BCL suppression.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Vitiello et al [112] used four different KRAS-mut CRC cell lines rendered resistant to a combination of cetuximab and refametinib (a selective MEK-inhibitor) and demonstrated that PI3K-AKT pathway activation acts as an escape mechanism in this setting. They showed that autocrine loops and heterodimerization of multiple receptors lead to the activation of several receptor tyrosine kinase, such as ERBB2, ERBB3 and IGF1R, whose signaling onto the PI3K/AKT pathway allows to bypass the block imposed by the double targeting of EGFR and MEK [112] . The effect on the response to cetuximab in the setting of the three most common AKT1 activating mutations found in CRC patients (i.e., E17K, E49K, and L52R) was recently investigated by overexpressing them in a cetuximab-sensitive KRAS-wt CRC cell line.…”
Section: Resistance To Anti-egfr Blockadementioning
confidence: 99%
“…Interestingly, all of them impaired the cytotoxic response not only toward cetuximab but also to chemotherapy. In addition, also the most common mutations of CTNNB1 (i.e., T41A, S45F, and S33P) were found to sustain resistance to the same agents [ 113 ] . These data indicate that possible therapeutic strategies to counteract the resistance to EGFR-targeted therapy would therefore be the use of inhibitors of the PI3K/AKT pathway.…”
Section: Resistance To Targeted Therapymentioning
confidence: 99%